Signaling Pathways Related to Oxidative Stress in Diabetic Cardiomyopathy - Peng, Meng-ling; Fu, Yu; Wu, Chu-wen; Zhang, Ying; Ren, Hang; Zhou, Shan-shan (Frontiers in Endocrinology, 2022)
Diabetes is a chronic metabolic disease that is increasing in prevalence and causes many complications. Diabetic cardiomyopathy (DCM) is a complication of diabetes that is associated with high mortality, but it is not well defined. Nevertheless, it is generally accepted that DCM refers to a clinical disease that occurs in patients with diabetes and involves ventricular dysfunction, in the absence of other cardiovascular diseases, such as coronary atherosclerotic heart disease, hypertension, or valvular heart disease. However, it is currently uncertain whether the pathogenesis of DCM is directly attributable to metabolic dysfunction or secondary to diabetic microangiopathy. Oxidative stress (OS) is considered to be a key component of its pathogenesis. The production of reactive oxygen species (ROS) in cardiomyocytes is a vicious circle, resulting in further production of ROS, mitochondrial DNA damage, lipid peroxidation, and the post-translational modification of proteins, as well as inflammation, cardiac hypertrophy and fibrosis, ultimately leading to cell death and cardiac dysfunction. ROS have been shown to affect various signaling pathways involved in the development of DCM. For instance, OS causes metabolic disorders by affecting the regulation of PPARα, AMPK/mTOR, and SIRT3/FOXO3a. Furthermore, OS participates in inflammation mediated by the NF-κB pathway, NLRP3 inflammasome, and the TLR4 pathway. OS also promotes TGF-β-, Rho-ROCK-, and Notch-mediated cardiac remodeling, and is involved in the regulation of calcium homeostasis, which impairs ATP production and causes ROS overproduction. In this review, we summarize the signaling pathways that link OS to DCM, with the intention of identifying appropriate targets and new antioxidant therapies for DCM.